New method for full-process deformation of slopes subject to drying-wetting cycles - Luo, Fangyue; Zhang, Ga (Bulletin of engineering geology and the environment, 2025)
Slope deformation due to drying-wetting cycles is a great concern in both the risk warning of slopes and the design of various slope structures on the slope. A new full-process slope deformation analysis method was derived based on slice methods, with innovations in terms of the constitutive equation, displacement compatibility equation, and stress equilibrium equation. A constitutive model of the soil was proposed with defined parameters, and it was reported to perform well in the prediction of the deformation increment and strength reduction due to drying-wetting cycles. The potential slip surface was shown to be a key component of characterizing the full-process deformation of a slope and to exhibit the displacement compatibility trend in which the relative horizontal displacement along the potential slip surface was equal at various locations. A slope deformation analysis algorithm was derived to analyze the shear deformation characteristics of potential slip surfaces and the volumetric deformation characteristics of sliding bodies subjected to drying-wetting cycles. The proposed method was validated by comparing the predicted slope deformation characteristics with centrifuge model test and field observation results under drying-wetting cycles. The method was confirmed to predict the full-process deformation of soil slopes during drying-wetting cycles, including the small deformation stage, prefailure stage, failure process and postfailure stage.